2005
DOI: 10.1002/pssb.200540093
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of electrons in a AlGaN/GaN QW: Effect of temperature, applied field, surface roughness and well width

Abstract: We study the dependence of low field mobility on various parameters such as well width and interface roughness for a two-dimensional electron gas confined to a AlGaN/GaN quantum well as a function of temperature. The potential profile, the energy levels, electron concentrations and wave functions for each level are found from the self-consistent numerical solution of Schrödinger and Poisson equations for the quantum well. Then the scattering rates for electrons due to acoustic phonons, optical phonons and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…It can be noted that there is a significant increase in peak velocity when the new parameters are used. decreases [33]. The peak velocity of GaN at 300 K is 2.75 × 10 7 cm/s at 140 kV/cm field, whereas that at 600 K is 2.25 × 10 7 cm/s at 170 kV/cm.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…It can be noted that there is a significant increase in peak velocity when the new parameters are used. decreases [33]. The peak velocity of GaN at 300 K is 2.75 × 10 7 cm/s at 140 kV/cm field, whereas that at 600 K is 2.25 × 10 7 cm/s at 170 kV/cm.…”
Section: Resultsmentioning
confidence: 77%
“…The scattering mechanisms mentioned in the previous section are considered in the ensemble Monte Carlo [27,33] simulation of electron transport in WZ InN and GaN. There are three sets of parameters used for InN ensemble Monte Carlo simulations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that the peak velocity increases while the field at which it is attained decreases as the temperature decreases for GaN. 37 For the traditional material parameter values of effective mass 0.11m 0 , gap energy 1.89 eV, and nonparabolicity value of 0.419 eV -1 resulting from the Kane model, a highest velocity value of 3.7 · 10 7 cm/s is attained in three dimensions under the given conditions for InN at 300 K at a field value of about 62 kV/cm, as seen in Fig. 3.…”
Section: Resultsmentioning
confidence: 97%
“…13,14 Low-field electron mobility as a function of temperature and ionized impurity concentration is extracted from the slope of the linear part of the velocity-field curves. Acoustic phonon, polar optical phonon, intervalley (equivalent and nonequivalent), ionized impurity, and alloy scatterings are the scattering processes used to obtain the low-field mobilities.…”
Section: Introductionmentioning
confidence: 99%